Studies on Kinetics, Isotherms, Thermodynamics and Adsorption Mechanism of Methylene Blue by N and S Co-Doped Porous Carbon Spheres - Yongpeng Ren; Feng Chen; Kunming Pan; Yang Zhao; Lulu Ma; Shizhong Wei (Nanomaterials, 2021)
Heteroatom-doped carbon is widely used in the fields of adsorbents, electrode materials and catalysts due to its excellent physicochemical properties. N and S co-doped porous carbon spheres (N,S-PCSs) were synthesized using glucose and L-cysteine as carbon and heteroatom sources using a combined hydrothermal and KOH activation process. The physicochemical structures and single-factor methylene blue (MB) adsorption properties of the N,S-PCSs were then studied. The optimized N,S-PCSs-1 possessed a perfect spherical morphology with a 2–8-μm diameter and a large specific area of 1769.41 m2 g−1, in which the N and S contents were 2.97 at% and 0.88 at%, respectively. In the single-factor adsorption experiment for MB, the MB adsorption rate increased with an increase in carbon dosage and MB initial concentration, and the adsorption reached equilibrium within 2–3 h. The pseudo-second-order kinetic model could excellently fit the experimental data with a high R2 (0.9999). The Langmuir isothermal adsorption equation fitted well with the experimental results with an R2 value of 0.9618, and the MB maximum adsorption quantity was 909.10 mg g−1. The adsorption of MB by N,S-PCSs-1 was a spontaneous, endothermic, and random process based on the thermodynamics analyses. The adsorption mechanism mainly involved Van der Waals force adsorption, π-π stacking, hydrogen bonds and Lewis acid–base interactions.